The journey from rhetoric to reality: participatory evaluation in a development context - and Chouinard, Jill Anne; Cousins, J. Bradley (Educational Assessment, Evaluation and Accountability, 2015)
In this paper, we focus on participatory evaluation in the context of international development and specifically on the emerging empirical knowledge base. In a prior review and critique of research on participatory evaluation (Cousins and Chouinard 2012), we examined 121 studies, with only 21 (17 %) situated in development contexts. However, the circumstances and challenges for international development and for development evaluation are distinct from those found in developed countries and therefore warrant separate consideration. To provide a more focused and detailed understanding of participatory evaluation in international development contexts, in this paper we augment our initial sample to a total of 40 studies on participatory evaluation in development published over the past 16.5 years. Based on an analysis of this research and related theoretical and conceptual contributions we identify and discuss eight emergent themes: multiplicity of relationships, consequences of stakeholder selection, characterization of participation, contextual complexity, methodological requirements, cultural influence, politics and power and learning and capacity building. We conclude with some reflections on an agenda for research.